If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20a + -13a + -21 = 0 Reorder the terms: -21 + 20a + -13a = 0 Combine like terms: 20a + -13a = 7a -21 + 7a = 0 Solving -21 + 7a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 7a = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 7a = 0 + 21 7a = 0 + 21 Combine like terms: 0 + 21 = 21 7a = 21 Divide each side by '7'. a = 3 Simplifying a = 3
| -5(2x-9)=2(x-7)-13 | | d(t)=1/3t-12 | | 19+2.50x=11+3.75x | | 3x-3=45-9x | | 9-3p=8p | | 3/2p-2=-7/9 | | 31-4r=-7(-4a+8) | | 3x^2+90=190-7x | | 2x+-5=12 | | 354=35t+.5*9.8*t^2 | | -24n^2=36n | | 2m^2+4=6m | | -2v-2v=-7(1+6r) | | 27=2m+5 | | Z^2+12Z-45=0 | | 20x6/14x2 | | 2m+37=67 | | 3-4x=-3x-2x | | -6.25=0.6x | | 2y+20=80 | | 5a+10b=45 | | -6x+18=-3(x-1) | | tan(x)=.48 | | 2(x-5)-3(2x+5)=5x+17 | | (8-i)(8+i)=0 | | 45t^2-72t+24=0 | | 3(8b+3)+6=36+3b | | 2(x-5)-3(2x+5)=5+17 | | 3p+5p=16 | | x+46=2x | | 2c-(c+6)=4(a-2) | | (10+i)-(3-5i)=0 |